Stress-Related Mental Health Disorders and Inflammation in Pregnancy: The Current Landscape and the Need for Further Investigation - Ravi, Meghna; Bernabe, Brandy; Michopoulos, Vasiliki (Frontiers in Psychiatry, 2022)
Many studies have focused on psychoimmunological mechanisms of risk for stress-related mental health disorders. However, significantly fewer studies have focused on understanding mechanisms of risk for stress-related disorders during pregnancy, a period characterized by dramatic changes in both the innate and adaptive immune systems. The current review summarizes and synthesizes the extant literature on the immune system during pregnancy, as well as the sparse existing evidence highlighting the associations between inflammation and mood, anxiety, and fear-related disorders in pregnancy. In general, pregnant persons demonstrate lower baseline levels of systemic inflammation, but respond strongly when presented with an immune challenge. Stress and trauma exposure may therefore result in strong inflammatory responses in pregnant persons that increases risk for adverse behavioral health outcomes. Overall, the existing literature suggests that stress, trauma exposure, and stress-related psychopathology are associated with higher levels of systemic inflammation in pregnant persons, but highlight the need for further investigation as the existing data are equivocal and vary based on which specific immune markers are impacted. Better understanding of the psychoimmunology of pregnancy is necessary to reduce burden of prenatal mental illness, increase the likelihood of a successful pregnancy, and reduce the intergenerational impacts of prenatal stress-related mental health disorders.